Robotic sectionectomy versus robotic hemihepatectomy for anatomic liver resection: a comparative analysis of perioperative outcomes - Birgin, Emrullah; Heibel, Marie; Téoule, Patrick; Reißfelder, Christoph; Rahbari, Nuh Nabi (Journal of robotic surgery, 2024)
Sectionectomy is a parenchma-sparing alternative to (extended) right or left hemihepatectomy. However, the effectiveness and safety of robotic sectionectomy (RS) versus robotic (extended) hemihepatectomy (RH) for the treatment of liver tumors remains unclear. We reviewed our prospective database for consecutive patients who had undergone robotic hepatectomies between March 2021 and July 2023 and included all patients with RS and RH. Demographic data, perioperative outcomes and long-term outcomes were analyzed and compared between both groups. Thirty patients met our inclusion criteria, of whom 16 patients underwent RS as opposed to 14 patients who underwent RH. Baseline characteristics were comparable between the study groups. The duration of Pringle maneuver was significantly longer in the RS group, while the remaining operative details were comparable. There were no significant differences in posthepatectomy outcomes between the study groups. All patients had negative resection margins. RS is a safe and effective parenchyma-sparing treatment modality.
Gesehen am 16.12.2024